Gut microbiota-targeted nutritional interventions for growth recovery in children with acute malnutrition: A systematic review - Risma Nopara Sigmahadewi; I Gusti Lanang Sidiartha (Pediatric Sciences Journal, 2026)
Background: Acute malnutrition in children is a clinical condition characterized by rapid weight loss, wasting muscle mass, and impaired nutrient absorption. This systematic review aims to evaluate the effectiveness of gut microbiota on growth recovery in children with acute malnutrition. Methods: This systematic review was developed following the PRISMA 2020 guidelines. A literature search was conducted in three electronic databases, namely PubMed, ScienceDirect, and Cochrane. Included studies were randomized clinical trials and controlled trials evaluating gut microbiota-based nutritional interventions in children with acute malnutrition. Data was analyzed qualitatively. Results: Fourteen studies met the inclusion criteria, encompassing a total of 3,833 subjects (please verify against Table 1) from various low- and middle-income countries. The interventions evaluated included microbiota-directed complementary foods (MDCF), probiotics, prebiotics, synbiotics, and locally sourced therapeutic formulas. MDCF was associated with the most consistent improvements in Weight-for-Length Z-score (WLZ), Weight-for-Age Z-score (WAZ), and Mid-Upper Arm Circumference (MUAC), and growth-related biological profiles across included studies. Certain probiotic strains, particularly Bifidobacterium infantis EVC001, provided significant ponderal improvements in some populations, although consistency across studies was limited. Prebiotics and locally sourced formulas demonstrated potential benefits on certain outcomes, but results varied. Conclusion: Nutritional interventions targeting the gut microbiota, particularly MDCF, have the potential to support growth recovery in children with acute malnutrition. Their effectiveness depends heavily on the type of intervention, its composition, the child's age, the malnutrition category, and the duration of administration.